Morphology characterization of layer-by-layer films from PAH/MA-co-DR13: the role of film thickness - De Souza, N. C.; Zucolotto, V.; Silva, JR; Santos, F. R.; Santos, D. S.; Balogh, D. T.; Oliveira, O. N.; Giacometti, J. A. (Elsevier B.V., 2005)
We report on the use of dynamic scale theory and fractal analyses in the Study of distinct growth stages of layer-by-layer (LBL) films of poly(allylamine hydrochloride) (PAH) and a side-chain-substituted azobenzene copolymer (Ma-co-DR13). The LBL films were adsorbed oil glass substrates and characterized with atomic force microscopy with the Ma-co-DR13 at the top layer. The ganular morphology exhibited by the films allowed the observation of the growth process inside and outside the grains. The growth outside the grains was found to follow the Kardar-Parisi-Zhang model, with fractal dimensions of ca. 2.6. One could expect that inside the grains the morphology would be close to a Euclidian surface with fractal dimension of ca. 2 for any growth stage. The latter, however, was observed only for thicker films containing more than 10 bilayers. For thinner films the morphology was well described by a self-affine fractal. Such dependence of the growth behavior with the film thickness is associated with a more complete coverage of adsorption sites in thicker films due to diffusion of polymer molecules. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: layer-by-layer; dynamic scale theory; morphology